1993
DOI: 10.1063/1.109514
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic switching of THz beams

Abstract: We demonstrate the use of a magnetic field to switch and to control the direction and polarization of a THz beam radiated from a semiconductor emitter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
35
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(37 citation statements)
references
References 9 publications
2
35
0
Order By: Relevance
“…The radiation intensity demonstrated asymmetrical dependence on the magnetic field inversion, as observed in the low field case. 4 The maximum intensity was obtained at approximately 3 T. This can be achieved even with a permanent magnet incorporating a special design. The total radiation power is estimated as approximately 80 W in average power from the InAs emitter.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The radiation intensity demonstrated asymmetrical dependence on the magnetic field inversion, as observed in the low field case. 4 The maximum intensity was obtained at approximately 3 T. This can be achieved even with a permanent magnet incorporating a special design. The total radiation power is estimated as approximately 80 W in average power from the InAs emitter.…”
mentioning
confidence: 98%
“…To overcome these limitations, simple and intense THz-radiation sources have been studied eagerly. 4 Previously, we reported significant enhancement of THz-radiation power from femtosecond-laser irradiated indium arsenide ͑InAs͒ in a magnetic field by the quadratic dependence of the magnetic field and excitation power. 5 We found saturation of THz-radiation power in a magnetic field, around 3 T. 6 However, the mechanism of such anomalous magnetic-field dependence has still not been clarified.…”
mentioning
confidence: 99%
“…2 Generally, both effects coexist in THz radiation from semiconductor surfaces. 3,4 Later the change of wave form and the increase in the amplitude of THz radiation were found for GaAs by applying external magnetic fields by Zhang et al 5 Sarukura et al have shown that InAs is a stronger THz emitter than GaAs and that the emission intensity increases monotonically with the external magnetic field intensity at least up to 1.7 T. 6 The enhancement of the radiation intensity under magnetic fields was confirmed for various semiconductors and the strongest radiation intensity was observed for InAs. 7 These results seem to hold promise for InAs as a compact strong THz emitter for THz spectroscopy and imaging without microfablication.…”
Section: Introductionmentioning
confidence: 93%
“…[2, 31 Using this technique the effects of magnetic and electric fields on the emission were also studied. [4,51 The dynamics of optically excited wavepackets in quantum well structures have also been studied using terahertz emission spectroscopy, leading to a demonstration of the existence of Bloch oscillations in superlattices. [6] Finally, terahertz emission spectroscopy has led to the detection of coherent infrared phonons in tellurium, [7] as well as the detection of coherent atomic vibrations in molecular crystals.…”
Section: Introductionmentioning
confidence: 99%